Sosialisasi Penerapan Health Related Fitness Model (HRV) kepada Guru Penjasorkes SD di Kabupaten Sumedang - Yudha M Saputra (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2023)
The Health Related Fitness (HRF) model is a learning model that is still rarely applied in Indonesia. The Health Related Fitness (HRF) model can be an alternative learning model that can be integrated with physical education in an effort to provide knowledge and habituation to practice physical activity for children at school. The Health Related Fitness model assumes that physical activity is the core of a healthy lifestyle, and that the development of such a lifestyle requires knowledge of physical fitness which includes the relationship between activity and health, healthy physical skills, and a commitment to the virtues of exercise. In this HRF model students are required to have self-management as one of the formal activities to make students have habits related to fitness training that are more meaningful for students in physical education settings. Therefore, the purpose of this socialization activity is to introduce the HRF model to Physical Education teachers in elementary schools so that it can be applied in the physical education learning process in order to increase the level of fitness and health status of students